Parâmetros sociocognitivos de construção de instrumento de representação temática da informação de áreas técnico-científicas - Oliveira, Greissi Gomes (Universidade Federal de São Carlos, 2013)
Information retrieval systems for information retrieval can occur through the search by author name, title of the work, by text words and through the theme or subject of a work. For accuracy in information search by subject, it becomes essential to use structured languages, called indexing languages, which are instruments with a view to enabling represent the contents of the collection. Thus, the theme of our research is to identify construction parameters of an instrument subject representation for information retrieval by subject in units of scientific and technical information (USTI). In this study, the units of scientific and technical information correspond to the libraries of the Federal Institute of Education, Science and Technology of São Paulo. Our research problem is characterized by the absence of social cognitive parameters for the construction of an instrument of representation of thematic information of technical and scientific areas. Identify proposed construction parameters of an instrument of thematic representation of information on the technical and scientific literature in the area of Knowledge Representation and Organization in the context of social cognitive librarian and user and the prospect of the units of scientific and technical information feds. Our overall objective was to present parameters for the construction of social cognitive instrument thematic representation of information techno-scientific areas. The specific objectives were: 1. identify the interdisciplinary Science, Technology and Society, Information Science, with emphasis on the Organization of Knowledge and Cognitive Science, to establish a collaborative dialogue in building a tool for thematic representation of information 2. present on the documentary languages, viewed as representation language for subject areas of technical and scientific information retrieval systems; 3. identify methods of construction of alphabetical indexing languages, given the technical and scientific literature in the area of Knowledge Representation and Organization in Information Science, 4. describe the context of social cognitive librarian and user units of scientific and technical information feds 5. the views of librarians and users of information units on federal technical-scientific parameters in the collaborative construction of an instrument subject representation in Science, Technology and Education, from the application of verbal protocol viewed as a qualitative methodology with sociocognitive approach. Our research is justified by the need for an indexing language for representation and retrieval of information in units of scientific and technical information to enable the correct representation of information by librarians in indexing activity and access to information for users seeking quality and specificity in recovery the information. As methodology we conducted bibliographic research on thematic Science, Technology, Society, Information Science, Cognitive Science, Knowledge Organization, Documentary Languages, Intelligence Units, Thesaurus, Federal Institute of Education. Subsequently, we apply the Protocol Verbal Group (PVG), knowing opinions of librarians and users on indicators for the construction of the instrument. The results were analyzed from grants acquired by literature accompanied by statements of participants and enabled PVG Eleven parameters indicate the collaborative construction of an instrument subject representation: 1. characterization of the user profile (target) that will make use of language learners and teachers of upper-level courses and medium 2. terms must serve the needs of representation and retrieval of information (guarantees and literary usage) 3. terms must originate in natural language and specialty (fair usage and literary) 4. terms should represent the vocabulary usage of the organization (organizational guarantee) 5. language must have both generic and specific terms; 6. language should promote control of synonyms; 7. language must identify the homonymous accordance with the use of qualifiers 8. establishment of logical-semantic relationships between terms of orders hierarchical, associative and equivalency; 9. inclusion of terms of scope notes when needed; 10. assignment of terms must be contemplating the balance between comprehensiveness and specificity achieved by the information retrieval system; 11. identification / building information retrieval system (catalog) that includes also factors such as being available online, offering reservation services online and renewal; allow viewing of information such as: cover, table of contents, introduction and full text materials contained in the collection of USTI; possess and to enable a feature suggestion terms, the timing of the search, both to fix the search expression as for the storage of subjects / search terms. This feature is important in terms of collection, aimed at updating process of language also from the user's perspective; provide and ensure accessibility of the language so that the librarian can realize the representation of information with it and from it, and allow available the accessibility of the language so that the user can perform a search by subject, for recovering useful information with it and from it. We believe that the diversity of the public pointed verbal protocols with respect to factors such as age, level of education (knowledge) and different areas of expertise, which makes us think and recommend to the IFSP USTI the construction and use of an indexing language with vocabulary arising from natural language and specialty (as in a thesaurus) but with the logical structure semantics between terms / headers from a list of subject headings, covering scope also notes that become necessary.
Socio-cognitives parameters for construction of tool for thematic representation of information techno-scientific areas
Keywords: Vocabulário controlado; Linguagem documentária alfabética; Sistemas de recuperação da informação; Metodologia sociocognitiva; Instituto Federal de Educação, Ciência e Tecnologia de São Paulo; Alphabetical indexing languages; Information retrieval systems; Sociocognitive Methodology; Federal Institute of Education, Science and Technology of São Paulo, IFSP; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA